2022
DOI: 10.18805/ijare.af-731
|View full text |Cite
|
Sign up to set email alerts
|

Role of Some Nanoformulations in Suppression of Silver Whitefly, Bemisia tabaci Population in Compared with Their Conventional Formulations in Tomato Fields

Abstract: Background: Scientific research will continue to search for the best methods to control the insect pests and at the same time reduce insecticide concentrations used. Using of nanoinsecticide formulations may be resolving this problem. Methods: In this work two types of formulations were used; nanoformulations and their conventional formulations. Three common insecticides were used against the silver whitefly, Bemisia tabaci; indoxacarb, spirotetramat and thiacloprid in tomato fields. The nanoparticle sizes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Also, it acts on a specific type of synapse located only within the brain and is protected by the blood-brain barrier (Hayes and Laws, 1990). On the other hand, imidacloprid showed effective activity against American serpentine leaf miner and whiteflies (Sabry et al, 2015 andYang et al, 2013). In addition, Schuster and Morris (2002) found that imidacloprid reduced the number of L. trifolii mines per plant in tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it acts on a specific type of synapse located only within the brain and is protected by the blood-brain barrier (Hayes and Laws, 1990). On the other hand, imidacloprid showed effective activity against American serpentine leaf miner and whiteflies (Sabry et al, 2015 andYang et al, 2013). In addition, Schuster and Morris (2002) found that imidacloprid reduced the number of L. trifolii mines per plant in tomatoes.…”
Section: Discussionmentioning
confidence: 99%